Differential expression of syndecans and glypicans in chronically inflamed synovium. Issue 5 (1st June 2007) - Patterson, A M; Cartwright, A; David, G; Fitzgerald, O; Bresnihan, B; Ashton, B A; Middleton, J
Abstract : Background: Membrane-bound heparan sulphate proteoglycans (HSPGs) act as co-receptors and presenters of cytokines and are involved in cell–matrix and cell–cell adhesion. Aim: To investigate which HSPGs are expressed in knee joint synovia from patients with different forms of arthritis and normal individuals. Methods: Synovial samples were obtained from patients with early rheumatoid arthritis (n = 8), longstanding rheumatoid arthritis (n = 13), psoriatic arthritis (n = 7), osteoarthritis (n = 6) and normal joints (n = 12). Expression of syndecan-1, -2, -3 and -4 and glypican-1, -3 and -4 was analysed by immunohistochemistry and dual label immunofluorescence. Results: The expression of HSPGs in chronically inflamed synovium exhibited a differential distribution. Syndecan-1 was present in the mononuclear infiltrates of synovia from patients with rheumatoid and psoriatic arthritis where it was expressed by plasma cells. Syndecan-2 was present mainly in blood vessels where it occurred on endothelial cells, pericytes and smooth muscle cells. Syndecan-3 stained intensely in endothelial cells but also occurred in sublining macrophages and the lining layer. Glypican-4 occurred in the lining layer and blood vessels. Increased expression of these HSPGs was apparent in rheumatoid and psoriatic compared to osteoarthritic and normal synovia. Little or no staining for syndecan-4, glypican-1 and glypican-3 was seen in all samples. Discussion: Selected HSPGs, such as syndecan-1, -2 and -3 and glypican-4, could play a part in the pathophysiology of arthritis, such as the migration and retention of leukocytes and angiogenesis in the chronically inflamed synovium.